Analysis of Factors Associated with Work-Related Distress Level Among Mechanics at PT X - Erwandi, Dadan; Tresnawati, Lena; Kadir, Abdul; Lestari, Fatma (Jurnal Ergonomi Indonesia (The Indonesian Journal of Ergonomic), 2022)
Distress is a negative form of psychosocial conditions that may be caused by work, family, social, and individual factors. Several incidents occurring at PT X have indicated the presence of distress among mechanics who work in the company, which is apparent from the physiological, psychological, behavioral, and cognitive symptoms experienced by these workers. This study aims to analyze the level of work-related distress, as well as factors influencing the level of distress experienced by mechanics at PT X. This was a cross-sectional study on all mechanics (n=37) working for PT X. Data analysis was performed using the chi-square test and logistic regression. Factors identified to be linked with distress level were organizational culture and function, interpersonal relations, work pressure, work-family conflict, task design, work schedule and working hours, exercise intensity, anxiety, emotional control, and smoking habits. Various factors have been identified as influencing the distress level among mechanics at PT X, with the emotional control factor as the factor with most influence on distress (Exp(B)=0.34). These factors require actions to reduce the risk of distress, such as providing better arrangement of overtime schedule and training.